Cryopreserved Cord Blood Serum for Reproductive Function Restoration During Antiphospholipid Syndrome - Trifonov, V. Yu.; Prokopyuk, V. Yu.; Zaychenko, A. V. (Problems of Cryobiology and Cryomedicine, 2011)
There was studied the influence of cord blood serum cryopreserved preparation Cryocell-Cryocord on reproductive system, gestation course and outcome of laboratory animals with experimental antiphospholipid syndrome (APS) and patients with APS. Preconceptional preparation with preparation CC together with traditional treatment of APS was shown to allow the avoiding of reproductive losses and maximal decrease of the number of complications during gestation due to the reduction of antibody concentration, normalization of homeostasis, improvement of blood supply in endometrium and placenta.